Inovasi Teknologi dan Sistem Informasi untuk Optimalisasi Penerimaan Pajak Daerah di Kabupaten Jember: Peran Bapenda dalam Meningkatkan Kinerja Keuangan - Zharifah Yustr Syifa' Hanifah; Devi Hardianti Rukmana (Lembaga Yasin AlSys, 2026)
Regional taxes are one of the main sources of locally generated revenue (Pendapatan Asli Daerah, PAD) and play a crucial role in supporting fiscal autonomy and financing regional development; however, their management still faces various challenges, including low taxpayer compliance, limited administrative systems, and suboptimal use of information technology. In line with the advancement of government digitalization, technological innovation and tax information systems have become critical strategies for enhancing the efficiency, transparency, and optimization of regional tax revenue. This study aims to analyze the effect of technological innovation and tax information systems on the optimization of regional tax revenue, as well as the role of the Regional Revenue Agency (Badan Pendapatan Daerah, Bapenda) in improving regional financial performance. The research employed a quantitative approach with primary data collected through questionnaires, while data analysis was conducted using multiple linear regression and path analysis to examine both direct and indirect effects among variables. The results show that technological innovation and tax information systems have a positive and significant effect on the optimization of regional tax revenue. Furthermore, the optimization of regional tax revenue has a significant effect on regional financial performance, with Bapenda acting as a mediating variable that strengthens this relationship. These findings underscore the importance of digital transformation in taxation, supported by Bapenda’s institutional capacity, in order to improve fiscal performance and regional financial autonomy.